(untitled) (Revista de Ciência Veterinária e Saúde Pública, 2022)
The application of spatial analysis tools for the study of canine visceral leishmaniasis can be influenced by the method used to detect dogs with leishmaniasis due to a large variety of available tests with distinct accuracy characteristics. Thus, a spatial comparison using two criteria of CVL infection/disease will be presented. The first has a combination of parasitological, molecular and serological techniques. The second uses serological tests recommended by the Ministry of Health in Brazil. It was observed that, indeed, the use of different diagnostic tests can have an important impact on spatial analyses.